TOEFL as a requirement for taking ECAP - Ramos Alfaro, Ana Carolina (Universidad de El Salvador, 2003)
Considering the importance that evaluations have for students who are in a significant stage in a major, it is extremely necessary to analyze the proper usage that a determined test has. This paper is addressed to focus on TOEFL test and point out the appropriateness it possesses for being used as a requirement for pre-graduating students from the major of “Profesorado en Inglés Para Tercer Ciclo de Educación Básica y Educación Media (Plan MINED)”. TOEFL Test lacks Validity in relation to the Specialized Area of the English Teaching Major, does not evaluate Oral Proficiency, it is not a reliable test because of the cultural aspects it has, it does not include any Pedagogical nor Didactical aspect for teaching the language, besides, the cost of $130.00US is not accessible for most of the students of the University of El Salvador that belong to this major, finally, the required score of 520 points does not comply with the results that can be obtained in relation to the academic background of students of the English Teaching Major of “Profesorado en Inglés Para Tercer Ciclo de Educación Básica y Educación Media (Plan MINED)”. The Ministry of Education determined the plans and programs of studies of the Teaching Majors based on the article 57 of the Law of Superior Education in the year 1997. These programs were initially executed by 13 institutions of higher Education in the year 1998 (Objetivos Curriculares de los Programas de Estudio del Profesorado en Inglés para Tercer Ciclo de Educación Básica y Educación Media, Plan MINED, Marzo de 2002). Making reference to some of the changes and applications that have been implemented specifically in the English Teaching Major, for instance, it can be mentioned, the requirement of an advanced level of English for those candidates of the major, furthermore, after finishing their studies, senior students are asked to take a test in which they are evaluated in their pedagogical and academical competences and are also demanded to get a minimal grade of 7.0 for students who graduate from the year 2003 on. This test is called ECAP (Instructivo para el Funcionamiento de Profesorado a partir del año 2003); and it has its legal bases on the Executive Agreement # 15-1913 with a date of November 1st , 2000, to be iimplemented since the year 2001 and it establishes “As a requirement to graduate of any teaching major since the year 2000, the approval of a Results Test that will be designed by the Ministry of Education” and also specified in the “Instructivo para el Funcionamiento de las Carreras de Profesorados”, given by the National Direction of Superior Education, Division of Teachers´ Formation, Chapter III. Literal B, Numeral 2